Foot Care Interventions for Patients with Type 2 Diabetes Mellitus Through A Home-Based and Family Involvement Approach - Prajayati Era (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
Type 2 diabetes mellitus is a chronic disease that can lead to serious complications, one of which is diabetic foot ulcers. Home-based foot care interventions involving families are considered an effective approach to improving care outcomes and preventing complications. Objective: This study aimed to review and synthesize scientific evidence regarding the effectiveness of home-based foot care interventions and family involvement in patients with type 2 diabetes mellitus. Methods: This study used a literature review design with a PICO approach. Articles were obtained from PubMed, ScienceDirect, and Google Scholar databases using the keywords: "diabetic foot care", "home-based intervention", "family caregiver", and "type 2 diabetes mellitus". Selection was based on predetermined inclusion and exclusion criteria, following the selection process of the Joanna Briggs Institute (JBI). Results: Of the 345 articles found, 7 suitable articles were selected. The synthesis results showed that educational and behavioral interventions involving families significantly improved knowledge, self-efficacy, foot care practices, and clinical outcomes such as wound healing and prevention of recurrent ulcers. Conclusions: Home-based foot care interventions involving families have been shown to be effective in improving self-management in patients with type 2 diabetes mellitus. The role of family education and support is crucial in sustainable foot care practices. Future studies are recommended to explore broader and more contextual interventions, especially in the elderly population and in areas with limited resources..